Solvent-free synthesis of enantioenriched β-silyl nitroalkanes under organocatalytic conditions - Dubey, Akhil K.; Chowdhury, Raghunath (Beilstein Journal of Organic Chemistry, 2021)
An enantioselective 1,4-conjugate addition of nitromethane to β-silyl α,β-unsaturated carbonyl compounds catalyzed by bifunctional squaramide catalysts has been developed. This methodology offers both enantiomers of β-silyl nitroalkanes in good to excellent yields (up to 92%) and enantioselectivities (up to 97.5% ee) under solvent-free conditions at room temperature. Control experiments reveal that the presence of a β-silyl group in the enones is crucial for high reactivity under the optimized reaction conditions.
Keywords: β-silyl α,β-unsaturated carbonyl compounds; β-silyl nitroalkanes; chiral organosilanes; organocatalysis; solvent-free synthesis